Factors Influencing Cervical Cancer Screening Participation in Female: Systematic Review - Hastuti, Sri; Wulan, Suryati Kumoro; Widyawati, Melyana Nurul (Indonesian Journal of Medicine, 2024)
Background: Cervical cancer is the second leading cause of morbidity and mortality in the world. This can be influenced by several things such as lack of willingness to participate in cervical cancer screening. This review aims to explore factors that influence participation in cervical cancer screening. Subjects and Method: This study is a systematic review with PICO covering: (1) Population: women; (2) Intervention: factors influencing participation; (3) none; (4) level of participation in cervical cancer screening. The databases used are PubMed and JSTOR. Inclusion criteria include full text in Indonesian and English with research subjects in women with cervical cancer. Exclusion criteria in this study were articles published less than five years ago. Results: A total of 21 articles stated that several factors such as interpersonal, intrapersonal, community, organizational, and public policy can influence participation in cervical cancer screening. Conclusion: Intervention strategies based on the reviewed factors need to be improved to reduce cervical cancer morbidity and mortality rates.